2015
DOI: 10.1002/qj.2539
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of turbulent flux reveals contrasting cooling potential for woody vegetation and grassland during heat waves

Abstract: We compared the capacity of woody versus grassy vegetation covers to buffer high temperatures during heat waves by partitioning turbulent heat between latent (λE) and sensible (H) fluxes, and quantifying advection using the Priestley-Taylor coefficient (α), for a16-year old grassland and an adjoining 6-year old plantation. We found that because λE dominated (>65%) the turbulent flux in the plantation and was at least twice as large as on the grassland (λE < 35% of the turbulent flux) during heat waves, the amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Therefore, if climate models incorrectly represent vegetation responses to drought, it is likely that they also erroneously represent feedbacks to the boundary layer (Donat et al , ). This hinders the capacity to capture any land surface amplification of climate extremes (Yunusa et al , ; Miralles et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if climate models incorrectly represent vegetation responses to drought, it is likely that they also erroneously represent feedbacks to the boundary layer (Donat et al , ). This hinders the capacity to capture any land surface amplification of climate extremes (Yunusa et al , ; Miralles et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…These processes resulted in enhanced cloud formation and convective precipitation over the restored areas. The maintenance of a positive feedback loop between the land surface and the atmosphere is a direct consequence of the ability of deep-rooted trees to extract moisture from the whole soil profile and maintain evapotranspiration during hot and dry conditions 17 44 . In contrast, shallow-rooted rainfed crops and pastures have a limited capacity to maintain this positive feedback.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest sensitivity to loss of forest and other woody vegetation cover is in arid and semi-arid regions, followed by temperate, tropical, and boreal biomes 10 . In the lower latitudes, forests play an important role in regulating climate at the regional scale by enhancing the partitioning of energy into latent heat, thereby impacting moisture recycling, convective precipitation and cloud formation 9 10 11 12 13 14 15 16 17 18 . This ability to maintain evaporative cooling of the land surface is a key biophysical process by which forests regulate the regional climate 9 10 11 12 13 14 .…”
mentioning
confidence: 99%
“…An afforestation study focusing on Europe by Galos et al (2013) reported increased precipitation (9-45 mm) and decreased temperature (up to 0.5 C) during summer season. In general, both radiative and non-radiative effect due to LULCC can play an important role in modulating the land surface climate ( Davin and de Noblet-Ducoudré, 2010;Bright et al, 2015;Yunusa et al, 2015; Syktus and McAlpine, 2016).…”
Section: Funding Informationmentioning
confidence: 99%